2014
DOI: 10.3892/mmr.2014.2523
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of scinderin modulates epithelial-mesenchymal transition markers in highly metastatic gastric cancer cell line SGC-7901

Abstract: Scinderin is a Ca2+‑dependent filamentous actin (F‑actin) severing and capping protein, which has a key role in regulated secretion. However, little is known regarding the function and mechanism of scinderin in human carcinoma development and progression. In the present study, the biological function of scinderin was investigated using a cell proliferation assay, flow cytometric analysis and a Transwell assay in highly tumorigenic and the metastatic human gastric cancer cell line SGC‑7901 transfected with scin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…In agreement with our report, SCIN expression levels were shown to correlate with poor overall survival in patients with gastric cancers, and silencing of SCIN effectively suppressed the migratory and invasive capabilities and tumourigenicity . SCIN knockdown upregulated the expression of E‐cadherin and decreased that of N‐cadherin and β‐catenin in the SGC7901 gastric cell line . Silencing of SCIN also inhibited the proliferation of human lung carcinoma cells .…”
supporting
confidence: 91%
“…In agreement with our report, SCIN expression levels were shown to correlate with poor overall survival in patients with gastric cancers, and silencing of SCIN effectively suppressed the migratory and invasive capabilities and tumourigenicity . SCIN knockdown upregulated the expression of E‐cadherin and decreased that of N‐cadherin and β‐catenin in the SGC7901 gastric cell line . Silencing of SCIN also inhibited the proliferation of human lung carcinoma cells .…”
supporting
confidence: 91%
“…As an important actin-binding protein, SCIN participates in actin-capping, -severing and -nucleating. It has been reported that knockdown of SCIN decreases the migratory capability of the highly metastatic GC cell line SGC7901 by promoting the epithelial-mesenchymal transition (EMT) [19]. In the present study, we found that SCIN expression was correlated with the invasion depth and lymph node metastasis of human GC, and associated with decreased survival of patients.…”
Section: Discussionsupporting
confidence: 61%
“…High SCIN expression has also been observed in human lung cancer specimens, and the level of SCIN is associated with cell proliferation in human lung carcinoma cell lines [17]. A quantitative proteomic analysis showed that SCIN was a cisplatin-resistant marker in the HT1376 human bladder cancer cell line [18], and SCIN knockdown effectively reduces cell proliferation and migration in the SGC7901 human GC cell line [19]. However, the clinical significance and the precise mechanisms that control SCIN expression in cancer have not been established.…”
Section: Scin Is Highly Expressed In Both Human Prostate Cancer Specimentioning
confidence: 99%
“…In lung and prostate cancer cell lines, SCIN-knockdown was demonstrated to inhibit cell proliferation (10,11), and SCIN was overexpressed in gastric cancer (12). SCIN-knockdown in gastric cell lines decreased the metastatic ability of these cells (13). These results suggest that SCIN may function as an oncogene.…”
Section: Introductionmentioning
confidence: 90%